Fictitious ideas, social facts and the double movement: Polanyi’s framework in the age of neoliberalism - Thomasberger, Claus (Karl Polanyi and twenty-first-century capitalism, 2020)
In the last decades, Karl Polanyi has gained recognition as one of the most important social scientists of the twentieth century. His seminal book, The Great Transformation, is listed among twentieth- century classics. How can this book, written more than seventy-five years ago, be applied to the current conditions? In order to answer this question the chapter not only compares the civilization of the nineteenth century in Europe with our own epoch. It also reconstructs some of Polanyi’s most important insights, such as his critique of the liberal utopia (in its classical and neoliberal version), his interpretation of the double movement, his vision of the meaning of the industrial revolution, his understanding of the problem of freedom in a complex society and his idea of a necessary ‘reform of human consciousness’. The chapter closes with a discussion of the question of how Polanyi’s categories can be used fruitfully so as to throw light to the post-war era and our society today.
Keywords: Great Transformation, The (Book); double movement; freedom in a complex society; liberal utopia; social facts